Security Requirements Classification into Functional and Non-Functional - Baraa KHAMAYSEH; Nabil ARMAN; Faisal KHAMAYSEH (Communications of International Proceedings, 2022)
Throughout the requirement engineering, the classification of user requirements has been a major concern of software engineering researchers. In this paper, we first highlighted the contributions of recent authors and researchers and their discussions regarding different methods of classification techniques. We mainly presented recent research endeavors that investigate the classification techniques regarding security requirements. We hence devoted a special concentration on security requirements definition as functional and non-functional as the first step in security requirements classification. Finally and by incorporating the different features of requirements, we determined the research gap towards future efforts to use some specified classification factors towards classifying security requirements into functional and non-functional requirements having in account the system and language features.
Keywords: Functional requirements; non-functional requirements; classification techniques; security requirements; security metrics.